EFFECTS OF FRINGE BENEFITS ON EMPLOYEES PRODUCTIVITY IN SELECTED ORGANISATIONS IN OGUN STATE, NIGERIA - Lawal, Musediq Olufemi (Annals of Spiru Haret University. Economic Series, 2021)
The study revealed that the provision of fringe benefits by the management of an organisation has positive roles to play in motivation of employees to higher productivity. It also defined the degree to which an employee identifies with the organization and wants to continue participating actively in it. Questionnaire was the major instrument adopted for this study, a total of 210 respondents were sampled from three food and beverages production organisations. Data generated through the questionnaires for the study were analysed making use of Statistical Package for Social Sciences (SPSS). The results showed that highly competitive fringe benefits have impetus for ensuring drastic reduction in labour turnover. Strong fringe benefits were therefore established to be correlated with employees’ motivation on the job, job satisfaction; job performance, employee retention and that proper workplace environment helps in reducing the rate of absentees. The study therefore submitted that application of fringe benefits facilitates effective productivity, while it was also discovered that employees’ involvement in organization activities contribute to organizational stability. The two hypotheses tested thus showed a significant relationship between employees’ involvement in policy formulation and implementation on individual productivity as well as organizational performance (F Statistic (17.65) P< 0.05 and sig. P< 0.05) and that significant relationship exists between application of fringe benefits and individual productivity as well as organizational performance (F Statistic (8.982) and sig. P< 0.05).